HUBUNGAN ANTARA EFIKASI DIRI DAN PERAN GURU DENGAN BELAJAR BERDASAR REGULASI DIRI PADA AKSELERAN - Andi Muthia Sari Handayani (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2018)
This research is a quantitative approach with the aim at knowing: (1). The relationship between self-efficacy and the role of the teacher by learning based on self-regulation. (2). The contribution given by self-efficacy and the role of teachers in self-regulation based learning. (3). Levels of self-efficacy and the role of teachers in learning based on self-regulation. The subject of this study was acceleration in one of the Public High Schools in Surakarta as many as 115 people. This study is a principled study on population studies. Based on the results and analysis using multiple regression it is known that the correlation coefficient R = 0.375 (p = 0.000: p <0.05), which means that there is a significant relationship between self-efficacy and the role of teachers with self-regulation. The total contribution given by the two independent variables in this study amounted to 14.1%, and for both categorizations the independent variables namely self-efficacy and the role of the teacher were at a high level, and the dependent variable of learning based on self-regulation was at a very high level. Key word: Self-Regulated Learning, Self-Efficacy, The Role of Teachers